2022
DOI: 10.1186/s12974-022-02615-7
|View full text |Cite
|
Sign up to set email alerts
|

SAFit2 reduces neuroinflammation and ameliorates nerve injury-induced neuropathic pain

Abstract: Background Neuropathic pain is experienced worldwide by patients suffering from nerve injuries, infectious or metabolic diseases or chemotherapy. However, the treatment options are still limited because of low efficacy and sometimes severe side effects. Recently, the deficiency of FKBP51 was shown to relieve chronic pain, revealing FKBP51 as a potential therapeutic target. However, a specific and potent FKBP51 inhibitor was not available until recently which hampered targeting of FKBP51. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 64 publications
(79 reference statements)
1
36
0
3
Order By: Relevance
“…Moreover, the highly potent FKBP51 inhibitor SAFit2 has been shown to pass the blood-brain barrier [7,8], indicating that SAFit2 is also able to pass the blood spinal cord barrier and can mediate analgesic effects in the central and peripheral nervous system. Likewise, we recently showed that SAFit2 ameliorates neuropathic pain in vivo as it counteracts the enhanced neuronal activity and reduces neuroinflammation after nerve injury [9]. These previous reports highlight the concept of FKBP51 inhibitors as a potential novel treatment approach for neuropathic pain.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Moreover, the highly potent FKBP51 inhibitor SAFit2 has been shown to pass the blood-brain barrier [7,8], indicating that SAFit2 is also able to pass the blood spinal cord barrier and can mediate analgesic effects in the central and peripheral nervous system. Likewise, we recently showed that SAFit2 ameliorates neuropathic pain in vivo as it counteracts the enhanced neuronal activity and reduces neuroinflammation after nerve injury [9]. These previous reports highlight the concept of FKBP51 inhibitors as a potential novel treatment approach for neuropathic pain.…”
Section: Introductionmentioning
confidence: 71%
“…Based on that, it might be beneficial to maintain the TRPV1 activity in a physiological state and to reduce its sensitization, which mainly occurs in inflammation-related pain states. In conclusion, the desensitizing effects of the C16 dihydroceramide further contribute to the analgesic effects of SAFit2, which are capable of mediating pain relief after neve injury [9].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations